Harmoni Antara Wahyu dan Sains: Analisis Qs. Nuh Ayat 14 dan Teori Evolusi - Hidayatullah, Sulis; Zafran, Rafiza; Deka, Nurafi Anti; Mutmainah, Hanifa; Kamalia, Rosyidah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the relationship between Surah Nuh verse 14 and the theory of evolution, focusing on the possibility of harmony between the teachings of revelation and scientific explanations of human origins. The main issue raised is the extent to which the verse can be interpreted contextually so as not to contradict the principles of biological evolution. This research uses a descriptive qualitative method with a thematic interpretation approach and a literature review of classical and contemporary literature, both from Islamic sources and modern science. The results of the analysis indicate that the term athwāran in Surah Nuh verse 14 implies gradual creation, which is semantically and contextually in line with the concept of gradual transformation in the theory of evolution. Furthermore, the Qur'an separates the physical and spiritual processes in human creation, allowing for an epistemological compromise between revelation and science. The conclusion of this study confirms that the integration of the two can enrich Muslims' understanding of human creation as a whole both biologically and spiritually without negating God's role as creator.